2019
DOI: 10.1152/ajpregu.00005.2019
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of catecholamine release from the adrenal medulla is altered in deer mice (Peromyscus maniculatus) native to high altitudes

Abstract: High-altitude natives have evolved to overcome environmental hypoxia and provide a compelling system to understand physiological function during reductions in oxygen availability. The sympathoadrenal system plays a key role in responses to acute hypoxia, but prolonged activation of this system in chronic hypoxia may be maladaptive. Here, we examined how chronic hypoxia exposure alters adrenal catecholamine secretion and how adrenal function is altered further in high-altitude natives. Populations of deer mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…This randomization procedure demonstrates that the D-statistics calculated for both genotypic comparisons were above the 99% quantile of the null distribution (Fig 3B inset). The pattern of down-regulation of catecholamine-related genes is consistent with recent findings that, compared to low-altitude deer mice from Nebraska, high-altitude mice express lower levels of DOPA decarboxylase in the adrenal medulla and exhibit reductions in catecholamine release from adrenal chromaffin cells [46]. Moreover, HIF-2α has been shown to be a positive regulator of catecholamine synthesis in adrenal chromaffin cells of rats [21], suggesting that the high-altitude Epas1 variant leads to a direct reduction in gene expression of enzymes involved in catecholamine biosynthesis, and thereby reduces circulating catecholamine levels.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This randomization procedure demonstrates that the D-statistics calculated for both genotypic comparisons were above the 99% quantile of the null distribution (Fig 3B inset). The pattern of down-regulation of catecholamine-related genes is consistent with recent findings that, compared to low-altitude deer mice from Nebraska, high-altitude mice express lower levels of DOPA decarboxylase in the adrenal medulla and exhibit reductions in catecholamine release from adrenal chromaffin cells [46]. Moreover, HIF-2α has been shown to be a positive regulator of catecholamine synthesis in adrenal chromaffin cells of rats [21], suggesting that the high-altitude Epas1 variant leads to a direct reduction in gene expression of enzymes involved in catecholamine biosynthesis, and thereby reduces circulating catecholamine levels.…”
Section: Resultssupporting
confidence: 87%
“…Elevated heart rates during hypoxia could also be a secondary consequence of adaptive changes in other functions of the cardiovascular control system that are the direct targets of selection. One possible target of selection is catecholamine release from the adrenal medulla, which we have recently shown is attenuated in high-altitude deer mice [46]. The genetic basis for this attenuation is unknown, but the patterns of variation in expression for genes related to catecholamine synthesis and release suggest that genetic variation in Epas1 may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Catecholamine synthesis and secretion by the adrenal gland is responsive to environmental hypoxia, and catecholamines can affect many physiological processes that impinge on oxygen delivery and consumption, including heart rate and vasoconstrictive responses ( Brown et al 2009 ). High- and low-elevation deer mice differ in their catecholamine response to hypoxia ( Scott et al 2019 ), and it is possible that these loci may contribute to this physiological difference. For example, previous work has shown that Epas1 , a two-way outlier, is a target of selection in deer mice and is associated with variation in heart rate under hypoxia ( Schweizer et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…exhibit blunted parasympathetic and sympathetic modulation of heart rate, in association with reduced expression of muscarinic m2 receptors and β 1 -adrenoreceptors in the cardiac ventricles (Pichon et al, 2013). A reduction in the importance of the sympathetic nervous system may also have evolved in high-altitude deer mice, in which catecholamine release from the adrenal medulla is blunted in association with reductions in the expression of enzymes involved in catecholamine biosynthesis (Scott et al, 2019;Schweizer et al, 2019). Although the mechanisms underlying the observed changes in HRV in high-altitude ducks remain to be discovered, our results here are consistent with these previous studies, suggesting that changes in autonomic tone may be involved in coping with the challenges at high altitude.…”
Section: Heart Rate Variabilitymentioning
confidence: 99%